Working Mother’s Experience with School-Age Children during the Covid-19 Pandemic: Working Mother’s Experience with School-Age Children during the Covid-19 Pandemic - Siska Ayu Tiara Dewi; Siti Editha Raisa; Sri Rezki Utami; Megawati Simanjuntak; Yulina Eva Riany (Journal of Family Sciences, 2022)
Working for women is part of self-actualization and to fulfil family needs. During the COVID-19 pandemic, the duties and responsibilities of working mothers have increased with the implementation of the school-from-home policy. Mothers also play a role as a teacher and assist in the child's learning process at home. The purpose of this study was to get an overview of the experiences of working mothers who have school-age children during the COVID-19 pandemic regarding the conditions experienced, the problems and challenges, and the strategies carried out in carrying out their duties and responsibilities. The study was a qualitative investigation using semi-structured interviews methods with three participants from Depok, Lampung, and Bangka Belitung. The interview process was carried out using the Zoom and Google-Meet online applications. The results showed that all participants acknowledged that there had been changes in work activities and daily routines during the COVID-19 pandemic, especially being a teacher for children at home. In the early of the COVID-19 pandemic, working mothers provide their own wisdom that there is more time with children and family. Although in general, they experience stress due to the demands of work, household, and assisting children to school from home.